Comparison of Open Lichtenstein Repair and Laparoscopic Transabdominal Preperitoneal of Inguinal Hernia: A Pragmatic RCT in Bangladesh - Sagar, SM Iftekhar Uddeen; Hossain, Mohammad Akram; Yusuf, Md Abdullah; Sultana, Rabeya; Azad, Md Abul Kalam (Journal of Current and Advance Medical Research, 2023)
Background: Laparoscopic inguinal hernia repair has emerged as an effective alternative to open Lichtenstein mesh repair for inguinal hernias. Objective: The purpose of the present study was to compare the surgical outcomes of laparoscopic trans-abdominal pre-peritoneal (TAPP) and open Lichtenstein mesh repair for the treatment of inguinal hernia. Methodology: This single centered, pragmatic randomized controlled trial was conducted in the Department of Surgery at 300 bed hospital, Narayanganj, Bangladesh from January 2018 to June 2020 for a period of two and half year. Patients who were presented with reducible, primary/recurrent, complete/incomplete inguinal hernias among male and female in more than or equal to 18 years of age were selected as study population. Lichtenstein mesh repair was performed which was compared with the laparoscopy group. Open Lichtenstein repair was done under spinal anesthesia with lightweight poly propylene mesh. Laparoscopy was performed by trans-abdominal pre-peritoneal (TAPP) technique under general anesthesia and heavy weight mesh was used. The hospital stay, operating time, post-operative complications like superficial wound infection, seroma formation, scrotal swelling as well as early recurrence and chronic groin pain were compared among these group. Results: A total number of 90 patients presented with inguinal hernia were recruited for this study of which TAPP was performed in 25 cases and 65 cases were undergone Lichtenstein repair. The mean age of laparoscopy and open group of patients were 49.28±9.9 years and 55.05±14.4 years respectively (p-0.03). The mean operation time was 85±10.31 minutes and 52.1±15.36 minutes in laparoscopy and open group respectively (p-0.000). The mean post-operative hospital stay was 2.9±0.78 days and 2.9±0.71 days in laparoscopy and open group respectively (p-0.94). In this study 21 (23.3%) patients developed 25 different early and late post-operative complications, out of which 15 (23.1%) in open group and 06 (23.3%) in laparoscopy group (p-0.52). One early recurrence was reported after 6 months follow up in laparoscopy group. Chronic groin pain was reported in 7 cases of which 5 (7.7%) cases in open group and only 2 (8.0%) cases in laparoscopy group (p-0.002). Conclusion: In conclusion the surgical outcomes of laparoscopic TAPP performed by a young surgeon in Bangladesh has given a clinically better result than open Lichtenstein repair considering hospital stay, seroma formation, wound infection, scrotal swelling and chronic groin pain. Journal of Current and Advance Medical Research, January 2023;10(1):35-40